2017
DOI: 10.1016/j.bjm.2016.07.025
|View full text |Cite
|
Sign up to set email alerts
|

The Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry (MALDI-TOF MS) identification versus biochemical tests: a study with enterobacteria from a dairy cattle environment

Abstract: Mastitis adversely affects milk production and in general cows do not regain their full production levels post recovery, leading to considerable economic losses. Moreover the percentage decrease in milk production depends on the specific pathogen that caused the infection and enterobacteria are responsible for this greater reduction. Phenotypic tests are among the currently available methods used worldwide to identify enterobacteria; however they tend to misdiagnose the species despite the multiple tests carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 18 publications
2
27
0
1
Order By: Relevance
“…MALDI-TOF MS and DNA sequence-based species classifications are comparable (Alatoom et al 2011, Rezzonico et al 2010, Verroken et al 2010, for instance Benagli et al (2012) validated 93% of MALDI-TOF MS-based Aeromonas species classifications by gyrB sequence analysis; considering that the remaining 7% were not identified because of missing reference spectra. These results corroborate also with Rodrigues et al (2017) who observed that gyrB sequencing and the MALDI-TOF MS technique produce similar results and thus could use the proteomic technique as a "gold standard" for evaluating the sensitivity and specificity of the phenotypic tests used in enterobacteria identification. The taxonomy of vibrios has been refined in recent years and the pyrH (uridylate kinase) gene has been validated as a high resolution taxonomic marker.…”
Section: Discussionsupporting
confidence: 89%
“…MALDI-TOF MS and DNA sequence-based species classifications are comparable (Alatoom et al 2011, Rezzonico et al 2010, Verroken et al 2010, for instance Benagli et al (2012) validated 93% of MALDI-TOF MS-based Aeromonas species classifications by gyrB sequence analysis; considering that the remaining 7% were not identified because of missing reference spectra. These results corroborate also with Rodrigues et al (2017) who observed that gyrB sequencing and the MALDI-TOF MS technique produce similar results and thus could use the proteomic technique as a "gold standard" for evaluating the sensitivity and specificity of the phenotypic tests used in enterobacteria identification. The taxonomy of vibrios has been refined in recent years and the pyrH (uridylate kinase) gene has been validated as a high resolution taxonomic marker.…”
Section: Discussionsupporting
confidence: 89%
“…The MALDI-TOF technique is also gaining ground for bacteria of veterinary importance, originating from bovine, ovine, porcine, and avian sources and, to a lesser extent, of canine, caprine, and equine provenance (Randall et al, 2015). Several researchers have applied the technique to bacterial groups causing bovine mastitis, such as group B streptococci (Barreiro et al, 2010), group D streptococci (Werner et al, 2012), non-aureus staphylococci (Barreiro et al, 2010;Cameron et al, 2017;Mahmmod et al, 2018), Enterobacteriaceae (Rodrigues et al, 2017;Savage et al, 2017), and even lactational mastitis in humans (Marín et al, 2017). Classical phenotypical and biochemical tests have limitations-they typically take from one to several days to perform and read, and misidentification of bacteria is not uncommon (Bes et al, 2000;Taponen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…CEUA-3664040915, Federal Rural University of Rio de Janeiro, Brazil). Routine biochemical tests identified 238 E. coli isolates, which was further confirmed by matrix-assisted laser desorption/ionization time-of-flight MS assay (Rodrigues et al, 2017;Santiago, 2017). Antimicrobial resistance of the E. coli isolates was obtained by the disk diffusion method, and two strains (G27 and S10) was suspected to AmpC hyperproduction.…”
Section: Methodsmentioning
confidence: 82%
“…The isolates were identified as E. coli by phenotypic laboratory tests in accordance with Koneman et al (2010). All E. coli were confirmed by matrix-assisted laser desorption/ionization time-of-flight MS assay (Rodrigues et al, 2017).…”
Section: Resultsmentioning
confidence: 99%